2013
DOI: 10.2478/rjes-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Affix Acquisition Order in Serbian EFL Learners

Abstract: Abstract:Given that affix knowledge plays a vital role in the development of L1/L2 knowledge, the aim of this paper is to explore Mochizuki and Aizawa's (2000)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
3
6
0
1
Order By: Relevance
“…Although some students indicated that they have more affixes knowledge than others, few of them could be said to have mastered the whole affixes lists. The score might be lower than the result of the study of Mochizuki & Aizawa (2000) and Danilovic et al (2013) involving Japanese and Serbian learners. This finding might not be surprising since the participants of the study were beginner EFL learners with a short history of learning English ranging from three years to four years starting from three years in junior high school.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although some students indicated that they have more affixes knowledge than others, few of them could be said to have mastered the whole affixes lists. The score might be lower than the result of the study of Mochizuki & Aizawa (2000) and Danilovic et al (2013) involving Japanese and Serbian learners. This finding might not be surprising since the participants of the study were beginner EFL learners with a short history of learning English ranging from three years to four years starting from three years in junior high school.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, it is important for students to have sufficient vocabulary although it should be borne in mind that having sufficient vocabulary knowledge does not necessarily mean that all else is easy since vocabulary knowledge is only one component of language skills (Schmitt, 1997). Besides, it should be understood that having vocabulary knowledge means that learners should also know other types of vocabulary knowledge such as knowledge of affixes, vocabulary size, and words association knowledge which are considered to have strong relationship among them (Danilovic, Savic, & Dimitrijevic, 2013;Mochizuki & Aizawa, 2000;Schmitt & Meara, 1997). This means that a person's knowledge of affixes, for instance, would probably help to increase both his/her vocabulary size and words association knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, knowledge of particular affixes did not correspond with their position in Bauer and Nation's scheme (e.g., the best known prefix in the study was re-, yet this appears at Level 6 in the scheme). In a replication of Mochizuki and Aizawa's study with upperintermediate Serbian learners, Danilović, Savić, and Dimitrijević (2013) likewise found partial knowledge of English affixes and an apparent order of acquisition at odds with Bauer and Nation's scheme. Ward and Chuenjundaeng (2009) had Thai learners of English give translations of base forms and of derived forms and found that in most cases where a base form was translated successfully, the derived form was not, and vice versa.…”
Section: Introductionmentioning
confidence: 66%
“…Third, the 1K band contains significantly fewer forms with Level 2 affixes only (e.g., accept-ed) and significantly more with affixes through to Level 3 (e.g.,. The actual difficulty of the affixes in Bauer and Nation's scheme has been questioned (Danilović, Savić, & Dimitrijević, 2013;Mochizuki & Aizawa, 2000), but it is the case that the 1K band has proportionally fewer forms featuring affixes that the scheme itself regards as easier. The 1K band, then, which should presumably be the starting point for learners and might be expected to contain the easiest words, in fact may pose the greatest challenge for learners.…”
Section: Discussionmentioning
confidence: 99%
“…MA also assists learners in recognizing the form-meaning links, identifying a syntactic category of the words, and producing new words in language use (Hayashi & Murphy, 2011;Schmitt & Meara, 1997;Sukying, 2017Sukying, , 2022. However, most studies have explored MA in native English children and L2 tertiary learners (Danilović, Savić, & Dimitrijević, 2013;Hayashi & Murphy, 2011;Mochizuki & Aizawa, 2000;Schmitt & Zimmerman, 2002;Sukying, 2018bSukying, , 2020Ward & Chuenjundaeng, 2009). However, little research has been conducted to explore primary school students' MA, particularly in an English as a foreign (EFL) context.…”
Section: Introductionmentioning
confidence: 99%